A BRIEF SKETCH OF THE MEMOIRS OF THE LIFE AND WORKS OF BEDIUZZAMAN SAID NURSI - Qaisar Mohammad (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Said Nursi was a profound Muslim thinker and revivalist, whose teachings (Risale-i Nur) and ideology are still being followed today in modern Turkey. His life is full of enthusiasm and energy. During his lifetime, he encountered problems similar to those faced by other Muslim scholars and thinkers in other parts of the Islamic world in the 20th century. He lived a life of struggle and harassment but never acted aggressively and never allowed his students to respond with aggression. The strong opposition of the government to religion as opposed to Nursi’s firm stand against any irreligiousness certainly made him a symbol of religious movement in Turkey. He sacrificed his whole life for the cause of Islam and fought against the corruption of society caused by enemies like atheism, materialism, colonialism, etc. through his writings collectively known as Risale-i Nur, whose teachings form the basis of one of the largest and rather influential religious orders. This paper anticipates discussing the significance of Nursi’s thoughts, teachings and his life and also explaining the importance of Nursi in the formation of ideology that helped the society of Turkey to get rid of anti-religious systems. The aim of this research paper is to explain his literary contributions that proved to be one of the most ubiquitous read materials in Turkey. Also, the paper will describe and highlight some clarity related to the writings of Nursi i.e. who wrote actually the treatises of Nursi, its propagation and popularization, who published and translated it in later times.